Altered Glutaminase 1 Activity During Neurulation and Its Potential Implications in Neural Tube Defects - Benavides-Rivas, Camila; Tovar, Lina Mariana; Zúñiga, Nicolás; Pinto-Borguero, Ingrid; Retamal, Claudio; Yévenes, Gonzalo E.; Moraga-Cid, Gustavo; Fuentealba, Jorge; Guzmán, Leonardo; Coddou, Claudio; Bascuñán-Godoy, Luisa; Castro, Patricio A. (Frontiers in Pharmacology, 2020)
The neurulation process is regulated by a large amount of genetic and environmental factors that determine the establishment, folding, and fusion of the neural plate to form the neural tube, which develops into the main structure of the central nervous system. A recently described factor involved in this process is glutamate. Through NMDA ionotropic receptor, glutamate modifies intracellular Ca2+ dynamics allowing the oriented cell migration and proliferation, essentials processes in neurulation. Glutamate synthesis depends on the mitochondrial enzyme known as glutaminase 1 (GLS1) that is widely expressed in brain and kidney. The participation of GLS 1 in prenatal neurogenic processes and in the adult brain has been experimentally established, however, its participation in early stages of embryonic development has not been described. The present investigation describes for the first time the presence and functionality of GLS1 in Xenopus laevis embryos during neurulation. Although protein expression levels remains constant, the catalytic activity of GLS1 increases significantly (~66%) between early (stage 12) and middle to late (stages 14-19) neurulation process. Additionally, the use of 6-diazo-5-oxo-L-norleucine (L-DON, competitive inhibitor of glutamine-depend enzymes), reduced significantly the GLS1 specific activity during neurulation (~36%) and induce the occurrence of neural tube defects involving its possible participation in the neural tube closure in Xenopus laevis embryos.